2021
DOI: 10.1111/bpa.12935
|View full text |Cite
|
Sign up to set email alerts
|

Mediators of cerebral hypoperfusion and blood‐brain barrier leakiness in Alzheimer’s disease, vascular dementia and mixed dementia

Abstract: In vascular dementia (VaD) and Alzheimer’s disease (AD), cerebral hypoperfusion and blood‐brain barrier (BBB) leakiness contribute to brain damage. In this study, we have measured biochemical markers and mediators of cerebral hypoperfusion and BBB in the frontal (BA6) and parietal (BA7) cortex and underlying white matter, to investigate the pathophysiology of vascular dysfunction in AD, VaD and mixed dementia. The ratio of myelin‐associated glycoprotein to proteolipid protein‐1 (MAG:PLP1), a post‐mortem bioche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 51 publications
2
46
1
Order By: Relevance
“…It is a progressive neurological disease associated with impairments in cognition and deterioration of the everyday life activities of an affected individual (Mills et al, 2007 ; Kirshner, 2009 ). In dementia, BBB breakdown and cerebral hypoperfusion cause brain damage and a decline in cognition (Nation et al, 2019 ; Tayler et al, 2021 ). Dementia is a considerable health complication affecting millions of people worldwide.…”
Section: Bbb Breakdown In Dementia (Including Ad and Vascular Dementia)mentioning
confidence: 99%
See 2 more Smart Citations
“…It is a progressive neurological disease associated with impairments in cognition and deterioration of the everyday life activities of an affected individual (Mills et al, 2007 ; Kirshner, 2009 ). In dementia, BBB breakdown and cerebral hypoperfusion cause brain damage and a decline in cognition (Nation et al, 2019 ; Tayler et al, 2021 ). Dementia is a considerable health complication affecting millions of people worldwide.…”
Section: Bbb Breakdown In Dementia (Including Ad and Vascular Dementia)mentioning
confidence: 99%
“…Figure 1 shows the difference between young or normal BBB and aged or dysfunctional BBB. (Bell and Zlokovic, 2009;Grinberg and Thal, 2010;Richardson et al, 2012;Rouhl et al, 2012;Sagare et al, 2012) Yes (Salmina et al, 2010;Villar-Vesga et al, 2020;Chacón-Quintero et al, 2021;González-Molina et al, 2021) Yes (Wardlaw et al, 2003;Zhang et al, 2014;Rajani et al, 2018;Wang et al, 2018;Tayler et al, 2021;Zhu et al, 2021) Extracellular components…”
Section: Phenotypes Of Bbb Breakdown In Normal Agingmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, studies have indicated that A β toxicity acts as a trigger of pyroptosis and BBB damage [ 14 , 15 , 34 ]. Therefore, a vicious circle is considered to form between astrocytic pyroptosis and A β accumulation in cerebral I/R injuries, exacerbating BBB damage which is a vital trigger of both AD and vascular dementia (VD), the two main types of dementia [ 35 ]. In the present study, our results exhibited the AQP-4 polarization loss with obvious dispersion accompanied with A β accumulation around astrocytes in ischemic cortex and hippocampus as well as increased A β 1–42 oligomers (the main form of A β toxicity) after cerebral I/R.…”
Section: Discussionmentioning
confidence: 99%
“…70 However, increased VEGF has been found in the white matter in patients with cSVD and AD without apparent rescue, suggesting that a more complex signaling mechanism is involved. 24 Loss of pericytes leads to increased VEGF-A expression in endothelial cells, 18 which may be a compensatory endothelial cell response to promote cell survival. However, it may also be attributable to loss of pericyte VEGF receptor 1, which regulates VEGF signaling by sequestration 110 or a combination of both mechanisms.…”
Section: Endothelial-pericyte Crosstalk In Angiogenesismentioning
confidence: 99%